2018
DOI: 10.1186/s12913-018-3212-9
|View full text |Cite
|
Sign up to set email alerts
|

Why do rural women in the most remote and poorest areas of Zambia predominantly attend only one antenatal care visit with a skilled provider? A qualitative inquiry

Abstract: BackgroundWhile focused antenatal care (ANC) has served as an entry point in the continuum of care for both mothers and children, fewer than a third of pregnant women in the most remote and poorest communities of Zambia achieve the four ANC visits recommended by the World Health Organization. Current evidence suggests that attending ANC provided by a skilled healthcare worker at least once is common and associated with skilled birth attendance. The aim of this study was to explain why one ANC visit with a skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…We also found a higher likelihood of timely ANC attendance among pregnant women of the richest wealth index compared to those of the poorest wealth index. The poorest women tend to suffer several challenges with respect to being able to afford health care as well as being capable of making decisions concerning their reproductive health and health promotive behaviors [ 41 ]. Hence, making them less likely to seek timely ANC attendance.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a higher likelihood of timely ANC attendance among pregnant women of the richest wealth index compared to those of the poorest wealth index. The poorest women tend to suffer several challenges with respect to being able to afford health care as well as being capable of making decisions concerning their reproductive health and health promotive behaviors [ 41 ]. Hence, making them less likely to seek timely ANC attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Research question/hypothesis/objectives clearly stated 98 (96) Description of the target population present 98 (96) Participant recruitment or sampling methodology described 100 (98) Methods section present 97 (95) Data analysis described 84 (82) Results presented 102 (100)…”
Section: Reporting Quality Indicator (N = 102)mentioning
confidence: 99%
“…The utilization of ANC services by rural area women during pregnancy is constrained by different problems [ 4 ]. A cross-sectional study from Nigeria showed that the national average of ANC utilization rate is 61%, of which 81% of them had ≥4 visits [ 5 ].…”
Section: Introductionmentioning
confidence: 99%